Gut Microbiota Changes in Patients With Major Depressive Disorder Treated With Vortioxetine - Ye, Xiaolin; Wang, Dong; Zhu, Huaqian; Wang, Dahai; Li, Jing; Tang, Yanqing; Wu, Jie (Frontiers in Psychiatry, 2021)
Vortioxetine hydrobromide is a common clinical medication for major depressive disorder (MDD). However, it is still unclear whether vortioxetine hydrobromide acts by affecting the structure and composition of gut microbiota. Here, we analyzed fecal samples from 28 healthy controls (HCs) and 26 patients with MDD before treatment with vortioxetine hydrobromide, at 4 weeks after treatment, and at 8 weeks after treatment. High-throughput pyrosequencing showed that according to the Chao1 and Shannon indices, fecal bacterial α-diversity was higher in the patients with MDD than in the HCs (p<0.05), but no significant differences after Vortioxetine hydrobromide treatment (p>0.05). PCoA results revealed that the gut microbiota composition were significant different between MDD groups and HCs. Proteobacteria and Actinobacteria strongly increased, whereas Firmicutes was significantly reduced in the MDD group compared with the HCs. After treatment with vortioxetine hydrobromide, Firmicutes significantly increased, and the proportion of Bacteroidetes decreased. Most notably, A negative correlation was observed between Lachnospira, Roseburia, and Faecalibacterium and the severity of depressive symptoms. Taken together, our data suggest that changes in the fecal microbiota composition in MDD patient compare with HCs, Vortioxetine hydrobromide may treat MDD through the regulation of gut microflora.